Direct-Acting Antiviral Therapy Produces High SVR12 in HCV GT-1 Cirrhotic Patients Regardless of Baseline Characteristics - Hoyle, Brian (MD Conference Express, 2014)
Treatment of cirrhotic, hepatitis C virus (HCV) genotype 1 (GT-1)-infected patients with a twice-daily oral regimen involving a single tablet of 3 direct-acting antiviral agents - the HCV NS3/4A serine protease inhibitor ABT-450 at 150 mg plus ritonavir 100 mg plus the NS5A inhibitor ombitasvir 25 mg - along with a tablet of dasabuvir 250 mg and a tablet of ribavirin yields high rates of sustained virologic response 12 weeks following conclusion of treatment. The findings of the large, international, phase 3 TURQUOISE-II trial are discussed in this article.